“SORRY” EXPRESS BY SENIOR HIGH SCHOOL STUDENT IN CIMAHI : SOCIAL CULTURAL EFFECT ON LANGUAGE - Ramadhan, Risky (PROJECT (Professional Journal of English Education), 2020)
Language is tool that use by human for communicate, and as tool to support them as social creature. Language is used by human every day in every situation, that make language become interesting phenomenon. During learning and teaching process that happen in class researcher find out the phenomenon that student use word “sorry” in context of asking permission not context for asking apology or expressing sympathy based on . Methodology of this research is qualitative with descriptive design. The instrument that use is observation, researcher is do observation in classroom activity on the class , and data is find from utterance that make by student during classroom activity. The result of this research most of student use word “sorry” in context of asking permission not for asking apologize. To understand the bigger concept of word sorry better to use bigger subject in research.